Research on the Impact of Digital Inclusive Finance on Urban Rural Integration Developmen: Taking the Yangtze River Delta Region as an Example - Shen, Rongfeng; Jiang, Ling (International Journal of Social Sciences and Public Administration, 2024)
The research on the impact of digital finance development on urban and rural integration can effectively integrate big data, 5G, blockchain and other digital technologies into urban and rural integration development with finance as the carrier, and maximize the use of new Internet technologies. This article first analyzes the significant achievements of digital inclusive finance in supporting rural revitalization, then analyzes the problems of digital inclusive finance in serving rural revitalization, and finally proposes countermeasures and suggestions.